(untitled) (Research, Society and Development, 2019)
Energy is an essential good for development, and its rational use is necessary to minimize environmental impacts and costs. Load monitoring has a very important role in this context, because it is necessary to know which devices are consuming the electric energy, how much, and at which moment it is consumed. The objective of this article is to perform a bibliometric research for qualitative and quantitative analysis on the identification of loads, especially the highly similar ones, including through of the use of reflectometry in this process. In the analyzes made in this work, it is verified that China is the country with the largest number of publications, followed by the United States. There is also a recent increase in publications on load identification, demonstrating that the topic has gained increasing relevance in the world scenario.